MINAT SISWA TERHADAP MATEMATIKA DAN HUBUNGANNYA DENGAN METODE PEMBELAJARAN DAN EFIKASI DIRI - Widyastuti, Widyastuti; Wijaya, Agung Putra; Rumite, Wayan; Marpaung, Rini Rita T (Mathematics Education Journal, 2019)
This study aimed to describe students' interest in mathematics and its relation with learning methode and self- efficacy. The population of this research were junior high school students in Bandarlampung. This is a quantitative descriptive research, studied 691 students which were selected using the stratified random sampling technique. Data in this study consisted of data on student’s interest in mathematics (Y), learning methode (X1), and student’s self-efficacy (X2) which were obtained using questionnaires. Data analized using correlation and multiple linear regression with α = 0.05. It were concluded that: (i) 22.58% of students have interests in high category, 76.56% with moderate category, and 0.86% in low category; (ii) there is a very strong positive relationship between the variables of learning method and self-efficacy together towards the variables of interest with a value of r = 0.844; (iii) there is a strong positive relationship between learning method and interest in mathematics when no change of self-efficacy with r = 0.505; (iv) there is a strong relationship between self- efficacy and interest in mathematics when the learning method does not change with r = 0.585; and (v) the formula of the linear regression model is Y = 22,788+0,972 X1+0,932 X2.DOI: 10.22342/jpm.13.1.6750.83-100